Deterrence and Defense - Snyder, Glenn H. (Glenn Herald), 1924-2013 (Book collections on Project MUSE., 1961)
In the literature of diplomacy and military strategy, there has long been a gulf between the concepts of deterrence and defense. Glenn Snyder bridges this gulf, offering a systematic analysis of the two ideas, with the aim of integrating them in a framework of theory. He proposes criteria for making rational decisions in national security policy and deals with the critical issue of the balance between deterrence of, and defense against, military attacks. The author augments the scattered literature on the subject with original contributions on this increasingly important facet of international relations. Originally published in 1961. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.